Peer-Impact Diagnosis and Therapy A Handbook for Successful Practice with Adolescents - Seltzer, Vivian Center (New York University Press, 2009)
Adolescents are infamous for their rebellious behavior. Indeed,much of the focus of therapy and clinical intervention with troubled adolescents focuses on their presumed need to rebel against their parents as they define their own identities. Yet psychologist Vivian Center Seltzer argues that approaching work with adolescent clients with this presumption in mind is likely to miss the roots of their problem behavior.Rather than acting out against parental authority, adolescents in need of clinical help are most often dealing with their disappointing comparisons with their peers—the most relevant others to them during this period of their development. Seltzer explains that it is countless interactions with their peers, at school and elsewhere outside of the home, that are the primary mode of psychological and social development for adolescents. Practitioners must recognize this crucial influence, and perhaps forgo traditional approaches, in order to better work with their adolescent clients.Peer-Impact Diagnosis and Therapy is a practical professional guide for how to approach and aid troubled teens by accessing the wealth of insight to be gained from understanding the influence of peer interactions on development and on behavior. Full of diagnostic categories and protocols for use with all types of adolescents, as well as guidance, tips, case studies, and offering a targeted model for adolescent group therapy, Seltzer provides professionals with all the tools they need to assist teens on their road to adulthood